Забезпечення надійності гідросистем сільськогосподарської техніки шляхом очищення робочих рідин - Журавель, Дмитро Павлович; Журавель, Дмитрий Павлович; Zhuravel, Dmytro (ТДАТУ, 2020)
UK: В роботі обґрунтована методика та устаткування для очищення робочих рідин з метою продовження строку їх служби і подальшого забезпеченням експлуатаційної надійності гідравлічних систем сільськогосподарської техніки. Розроблено та досліджено математичні моделі надійності системи очищення відпрацьованих гідравлічних олив. Отримано ймовірності станів, які покладені в основу визначення комплексних показників надійності гідравлічної системи сільськогосподарської техніки. В цілому надійність всієї гідравлічної системи залежить від надійності всіх її елементів, а також від якісних показників робочих рідин. Приведена технічна характеристика установки для очищення відпрацьованих гідравлічних олив та її принцип дії. RU: В работе обоснована методика и оборудование для очистки рабочих жидкостей с целью продления срока их службы и дальнейшего обеспечением эксплуатационной надежности гид-равличних систем сельскохозяйственной техники. Разработаны и исследованы математические модели надежности системы очистки отработанных гидравлических масел. Получены вероятности состояний, которые положены в основу определения комплексных показателей надежности гидравлической системы сельскохозяйственной техники. В целом надежность всей гидравлической системы зависит от надежности всех ее элементов, а также от качественных показателей рабочих жидкостей. Приведена техническая характеристика установки для очистки отработанных гидравлических масел и ее принцип действия. EN: The work substantiates the methodology and equipment for cleaning working fluids with the aim of extending their service life and further ensuring the operational reliability of hydraulic systems of agricultural machinery. Oil contamination can lead to: deterioration of hydraulic equipment and reduced efficiency; accelerating the process of oxidation of oil; to oil decomposition, emulsification, rust and corrosion; deformation of the pump and the rod of the hydraulic cylinder; failure of valves; development, wear of seats of spools, their jamming; failure of hydraulic motors and hydraulic pumps; wear, jamming of plunger pairs, rocking nodes; failure of the hydraulic distributor; increased wear of seals of hydraulic cylinders, hydraulic motors, hydraulic pumps, etc .; hydraulic system overheating. Therefore, to extend the life of the oils and machinery mechanisms, it is necessary to carry out their planned replacement or cleaning with the help of special filtering equipment. Mathematical models of the reliability of the system for cleaning used hydraulic oils have been developed and investigated. The probabilities of the states that underlie the definition of complex indicators of the reliability of the hydraulic system of agricultural machinery are obtained. In general, the reliability of the entire hydraulic system depends on the reliability of all its elements, as well as on the quality indicators of the working fluids. The main existing methods of purification of chemical-chemical indicators of working fluids are substantiated. The technical characteristic of the installation for cleaning used hydraulic oils and its operation principle are given.
Обеспечение надежности гидросистем сельскохозяйственной техники путем очистки рабочих жидкостей
Hydraulic system reliability agricultural machinery by cleaning working liquids
Keywords: система очищення; надійність системи; відпрацьована гідравлічна олива; фільтрація; граф станів; інтенсивність і ймовірність відмови; інтенсивність відновлення; ресурс; система очистки; надежность системы; отработанное гидравлическое масло; фильтрация; граф состояний; интенсивность и вероятность отказа; интенсивность восстановления; cleaning system; spent hydraulic oil; system reliability; filtration; state graph; failure rate and probability; recovery rate; resource